Training Teachers with a Virtual Learning Community: Connecting Peers with an International Dimension - García Fernández, Beatriz; Jiménez, Antonio Mateos; Bejarano Franco, María Teresa (Pedagogika, 2016)
Here we present research into the use of a virtual learning community in formal teacher training to determine the associated pedagogical benefits. The community was used by 876 teacher candidates, graduate teachers and university teachers from Spain, Chile and Belgium. Using it resulted in benefits relating to the transfer of knowledge and pedagogical experiences, cooperative and collaborative work, teacher coordination and contextual diversity, and it has been highly valued by the participants.